Wing reduction and body size variation along a steep elevation gradient: a case study with Magellanic sub-Antarctic mayflies and stoneflies - Rendoll-Carcamo, Javier; Ganan, Melisa; Madriz, R. Isai; Convey, Peter; Contador Mejias, Tamara Andrea (My University, 2023)
Introduction: Ecogeographical patterns in body size have been described across a wide range of vertebrate species. However, insects have shown inconsistent patterns in studies to date. Aquatic insects, particularly those from remote regions, have barely been explored. Methods: The Magellanic sub-Antarctic ecoregion offers an ideal natural laboratory with near pristine environments, limiting the potential influence of confounding variables. In this study, we evaluated the influence of elevation on body and wing size and aspect ratio patterns for 10 species of mayfly (Ephemeroptera) and stonefly (Plecoptera) along a steep coastal elevation gradient (similar to 0-600 m a.s.l.). Results: We detected significant relationships between altitude and morphological features for the studied species. Additionally, we found that in females, morphological changes were slightly more pronounced than in males, probably due to their role as dispersers. While body size showed an increase along the elevation gradient, there was a notable decrease in some species' wing length over a relatively short geographic distance. Discussion: Our data suggest that morphological plasticity might be promoted in response to the harsh environmental conditions that typify the steep coastal Magellanic sub-Antarctic mountain ranges.
Keywords: body size; ecogeographical patterns; ephemeroptera; plecoptera; sub-antarctic; wing reduction